Coastline dynamics at Thukela Mouth and the Amatigulu and Umlalazi river estuary areas KwaZulu-Natal - Sumner, P.D. (Paul) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.